2009
DOI: 10.1073/pnas.0811370106
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-induced changes in elongation factor Tu conformation control GTP hydrolysis

Abstract: In translation, elongation factor Tu (EF-Tu) molecules deliver aminoacyl-tRNAs to the mRNA-programmed ribosome. The GTPase activity of EF-Tu is triggered by ribosome-induced conformational changes of the factor that play a pivotal role in the selection of the cognate aminoacyl-tRNAs. We present a 6.7-Å cryo-electron microscopy map of the aminoacyl-tRNA⅐EF-Tu⅐GDP⅐kirromycin-bound Escherichia coli ribosome, together with an atomic model of the complex obtained through molecular dynamics flexible fitting. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
186
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(206 citation statements)
references
References 33 publications
9
186
1
6
Order By: Relevance
“…The present study (2), together with the previous cryo-EM reconstructions of the same complex and the X-ray structures of the ribosome (4), identified several potentially important contacts that may help to induce and stabilize the active conformation of EF-Tu on the ribosome. On codon recognition, the 30S subunit switches to a closed conformation, in which the codon-anticodon duplex is stabilized, presumably involving an interaction with protein S12 (2,11). It is possible that the contact between the switch I region of EF-Tu and helices 8 and 14 in the 30S subunit requires the closed conformation of the 30S subunit, which would imply a direct link between changes in the decoding center and GTPase activation.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…The present study (2), together with the previous cryo-EM reconstructions of the same complex and the X-ray structures of the ribosome (4), identified several potentially important contacts that may help to induce and stabilize the active conformation of EF-Tu on the ribosome. On codon recognition, the 30S subunit switches to a closed conformation, in which the codon-anticodon duplex is stabilized, presumably involving an interaction with protein S12 (2,11). It is possible that the contact between the switch I region of EF-Tu and helices 8 and 14 in the 30S subunit requires the closed conformation of the 30S subunit, which would imply a direct link between changes in the decoding center and GTPase activation.…”
supporting
confidence: 70%
“…The reason for this difference is not clear, but it underlines the importance of high resolution in structural studies. Arg-58, which is located in the switch I region of EF-Tu in a position homologous to that of the catalytic arginine in G␣ proteins, is not essential for GTP hydrolysis by EF-Tu (12), in keeping with its position in the present structure (2).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…eEFSec GTPase Activity Is Regulated by Domain IV-The activation of translation GTPases, such as eEF1A, is achieved through conformational changes induced by the ribosome (30,31). Previous work with SelB, the Sec-specific elongation factor in bacteria, demonstrated that 70 S ribosomes increased the GTPase activity only when a bacterial SECIS element was present (32).…”
Section: Resultsmentioning
confidence: 99%
“…In that sense, our approach bears an analogy with the use of low-resolution Cryo-EM in combination with atomistic modeling to produce fully atomistic models of large structures (93), including chromatin components (94,95). Unlike Cryo-EM, our approach can be used at ambient conditions.…”
Section: Discussionmentioning
confidence: 99%